Short communication: Viable Mycobacterium avium subspecies paratuberculosis in retail artisanal Coalho cheese from Northeastern Brazil - Schwarz, D. G. G. (2014)
Mycobacterium avium ssp. paratuberculosis (MAP) is the etiologic agent of paratuberculosis and it potentially plays a role in Crohn’s disease. In humans, the main route of transmission of MAP might be the intake of contaminated milk and dairy products. Considering that MAP has already been detected in many types of cheese in different counties, and that Coalho cheese is an important dairy product in northeastern Brazil, the aim of this study was to report the first detection of MAP in retail Coalho cheese in Brazil by PCR and culture. Of 30 retail Coalho cheese samples, 3 (10%) amplified fragments of a similar size to that expected (626 bp) were obtained and viable MAP was recovered by culture from 1 (3.3%) sample. The DNA from the positive culture sample was sequenced and showed 99% identity with the insertion sequence IS900 deposited in GenBank. It was possible to identify the presence of MAP-specific DNA in the analyzed samples for the first time in Brazil, and to recover viable cells from retail Coalho cheese.